Removal mechanism of mitoxantrone by a green synthesized hybrid reduced graphene oxide @ iron nanoparticles. (May 2020) - Wu, Jing; Lin, Ze; Weng, Xiulan; Owens, Gary; Chen, Zuliang
Abstract: Anti-tumor drugs, due to their non-specific toxicity will cause long-term delayed toxicity to organisms and humans when discharged into the environment. In this study, reduced graphene oxide @ iron nanoparticles (rGO@Fe NPs) were successfully prepared using green tea extract as reductant and subsequently used for mitoxantrone (MTX) removal. SEM and Raman spectroscopy showed that 30–60 nm sized Fe NPs were loaded on rGO and green tea extract successfully reduced GO to rGO. The removal efficiency of MTX by the hybrid material was higher (98.5%) than either rGO (77.5%) or Fe NPs (53.1%) alone. In addition, the removal efficiency of MTX by the hybrid material was as high as 95% within 5 min, MTX adsorption followed both a pseudo-second-order kinetic model and the Langmuir isotherm, and it is a spontaneous adsorption. Recycling experiments showed that the removal efficiency of MTX decreased from 99.9 to 76.8% after six cycles, and could be as high as 99% in both municipal and medical wastewater. Scanning electron microscopy (SEM), Fourier transform infrared Spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and High performance liquid chromatography (HPLC) were all used to characterize and analyze the hybrid material, and possible adsorption mechanisms which revealed that MTX adsorption probably involved a combination of π-π stacking interaction, hydrogen bonding, electrostatic interaction and pore-filling. Graphical abstract: rGO@Fe NPs was successfully synthesized using green tea extract as a reducing agent, exhibiting both an excellent adsorption capacity and a fast adsorption rate to mitoxantrone. Image 1 Highlights: Green synthesis of hybrid rGO@Fe NPs by plant extract. More than a 98.5% mitoxantrone was removed. The removal mechanism involved a π-π stacking interaction. The removal of mitoxantrone from wastewater was demonstrated.